PREVALANCE OF STRESS AMONG HEALTHCARE WORKERS IN SAUDI ARABIA - Afaf Abdullatif Alkhamis, Jaber Hadi Hussein Lasloom, Marzoug Ali Hadi Al-Mahamid, -Wabran Salem Saleh Alkhreem, Khalid Naser Naser Alnaser, Hamad Mesfer Salem Alyami (Chelonian Research Foundation, 2022)
Introduction: Factors leading to workers' stress include role overload, poor learner behavior, lack of resources, hospital size, diversity in individuals with whom they have to work, and lack of motivation from coworkers. This study aimed to assess stress among healthcare workers working in Saudi Arabia. Methods: This is a cross-sectional observational study design conducted on health workers using an online questionnaire in Saudi Arabia. The total number of hospital healthcare workers does not exceed 430 workers. We assumed that the confidence level is 95% and the error Of estimation is 5%. Based on the equation Of sample size calculation for proportion (below), we use epi-info software (Statistical package). "Hie sample size after correction for population size (which is a small population in this study) is 203 workers. Results: The majority of respondents (64.5%) were aged below 30 years, 31% were aged 31-50 years (middle), and 4.4% were aged more than 50 years (Old). The majority Of respondents were healthcare workers (96.1%) while 3.9% held managerial positions. More than 73% of the respondents were working in one school, 15.3% hospitals and 11.3% were working in more than 3 hospitals. A number of 97% (47.8%) sometimes were feeling that they were capable of making decisions at the hospital. Most of the respondents 58.1% sometimes were feeling that most problems they were encountering at the hospital could be surmounted. The majority of respondents were sometimes (54.2%) feeling happy at work, 33% were mostly and 12.8% often had that feeling. Conclusions: There is a considerable amount of stress among healthcare workers in Saudi Arabia. Females aged below 30 years were found sometimes more significantly feel capable Of making decisions at hospitals compared to males. While males aged 31-50 years were sometimes more significantly felt capable of making decisions at hospitals compared to females. However, the study showed that those aged below 30 years were significantly greater feel capable of making decisions at the hospital compared to those aged 31-50 years and those aged above 50 years. Keywords: Health workers, Hospitals, Stress, Burnout, Saudi